2021
DOI: 10.1111/dom.14387
|View full text |Cite
|
Sign up to set email alerts
|

Association of estimated plasma volume and weight loss after long‐term administration and subsequent discontinuation of the sodium‐glucose cotransporter‐2 inhibitor tofogliflozin

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT2) are drugs that have been reported to have several effects through the regulation of plasma volume, for example, antihypertensive effects. This study aimed to clarify the impact of long-term administration and subsequent discontinuation of the SGLT2 inhibitor tofogliflozin on estimated plasma volume (ePV), brain natriuretic peptide (BNP) and the relationship between changes in ePV, BNP and body weight (BW). Data from 157 participants with type 2 diabetes receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…On the basis of a comprehensive review, we identified 15 studies that evaluated the effect of SGLT2 inhibitors on plasma volume (Table 2). 64,[72][73][74]78,[98][99][100][101][102][103][104][105][106][107][108][109] Unfortunately, most studies estimated changes in plasma volume using the Kaplan-Hakim and Strauss formulae, which cannot be applied to the evaluation of changes produced by SGLT2 inhibitors. Four reports 64,72,74,109 used indicator dilution methods, and of these, 3 were double blind and placebo controlled.…”
Section: Effect Of Sglt2 Inhibitors On Plasma and Blood Volume In Cli...mentioning
confidence: 99%
“…On the basis of a comprehensive review, we identified 15 studies that evaluated the effect of SGLT2 inhibitors on plasma volume (Table 2). 64,[72][73][74]78,[98][99][100][101][102][103][104][105][106][107][108][109] Unfortunately, most studies estimated changes in plasma volume using the Kaplan-Hakim and Strauss formulae, which cannot be applied to the evaluation of changes produced by SGLT2 inhibitors. Four reports 64,72,74,109 used indicator dilution methods, and of these, 3 were double blind and placebo controlled.…”
Section: Effect Of Sglt2 Inhibitors On Plasma and Blood Volume In Cli...mentioning
confidence: 99%
“…Rapid attenuation of PV at 12 weeks has been shown with canagliflozin in patients with T2DM [11]. Finally, in the longest available study, long-term monotherapy with tofogliflozin in patients with T2DM produced a significant decrease in estimated PV 52 weeks post-initiation of treatment, however, that effect was rapidly ameliorated [12].…”
Section: Resultsmentioning
confidence: 91%
“… 12 Previous studies have reported that SGLT2 inhibitors reduced both the plasma volume measured by 125 I‐labelled human serum albumin and ePV by using laboratory data in patients with T2DM. 18 , 19 Other studies have also reported that SGLT2 inhibitors reduced the ePV in patients with T2DM complicated by cardiovascular diseases or HFrEF. 20 , 21 In addition, SGLT2 inhibitors reduced pulmonary arterial pressure in patients with heart failure.…”
Section: Discussionmentioning
confidence: 97%
“…Sodium glucose co‐transporter 2 inhibitors have some favourable effects on heart failure beyond their glucose‐lowering effects 12 . Previous studies have reported that SGLT2 inhibitors reduced both the plasma volume measured by 125 I‐labelled human serum albumin and ePV by using laboratory data in patients with T2DM 18,19 . Other studies have also reported that SGLT2 inhibitors reduced the ePV in patients with T2DM complicated by cardiovascular diseases or HFrEF 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation